(untitled) (Acta Scientiarum. Agronomy, 2025)
Drought is an environmental condition that compromises the development of coffee plants. New coffee genotypes that are resistant to drought must be selected quickly and practically. The objectives of this study were to evaluate the resistance of five genotypes of Coffea arabica, including three new genotypes with introgression of genes from Coffea racemosa (H0113-40-26-1, H0113-40-26-19, and H0113-40-26-10), to water restriction and relate the intensity of plant wilting with physiological responses and nutrient accumulation. The experiment was conducted using 45 coffee seedlings obtained from seeds with six pairs of leaves cultivated in tubes. Some seedlings were subjected to two water restriction periods, whereas the remainder were kept under irrigation. The photosynthesis rate, transpiration rate, and wilting intensity were evaluated after each restriction period. Nutrient content was also evaluated after two periods of water restriction. The evaluation of wilting intensity corroborated the physiological parameters. There was a reduction in photosynthesis and transpiration rates under water restriction and nutrient accumulation in coffee seedlings H0113-40-26-1, H0113-40-26-19, and H0113-40-26-10 increased under these conditions. C. arabica genotypes carrying the genes of C. racemosa presented good drought resistance, with H0113-40-26-10 being the most resistant and showing the lowest wilt intensity.